Consumer Response to The Increase in Clothing Prices Ahead of Eid - Siti Alfia; Muzalifah Muzalifah (Jurnal Ekuilnomi, 2026)
This study aims to analyze consumer responses to rising clothing prices ahead of Eid al-Fitr in Palangka Raya City. The focus is on how consumers cope with seasonal inflation and the strategies they employ in making purchasing decisions. The study employs a qualitative approach using field research methods, including interviews, observations, and data triangulation. The results indicate that price increases are perceived as a normal annual phenomenon, yet they still prompt consumers to make adjustments such as comparing prices, taking advantage of promotions, and prioritizing family needs. These findings confirm that economic, social, and cultural factors play a role in shaping consumption behavior ahead of Eid al-Fitr. This study has practical implications for merchants and policymakers. Merchants are expected to set prices fairly and transparently and provide promotions relevant to consumer needs, while policymakers need to strengthen market oversight and maintain price stability to protect the purchasing power of the public particularly low- and middle income groups from the impact of seasonal inflation